The role of social capital in competition and gender-matching environments: Evidence from East Asian countries - Seo-Young Cho (Philipps-University Marburg, School of Business and Economics, 2017)
This paper investigates the role of social trust in determining one's willingness to compete in math competitions in school, observing how competitive occupational choices often require higher quantitative skills. Using the data of the PISA test in math, the empirical results highlight that a higher level of trust in school environments promotes a student's willingness to participate in math competitions. However, this positive effect of trust maintains mainly in mixed-sex competition, but not in single-sex competition. Furthermore, the effect of trust on mixed-sex competition is greater for girls than boys, while the effect is equally insignificant for boys and girls in single-sex competition. These findings suggest the importance of trust in the rules of the game when girls are matched with boys. On the other hand, when they compete with other girls, concerns about fairness do not play a significant role in their consideration. This is possibly because single-sex matches reduce unfairness caused by gender discrimination.
Keywords: I24; J16; O17; O53; 330; gender; competition; math studies; social trust; gender-matching school environments; institutions; survey; East Asia